Vorstellung der Landesinitiative openaccess.nrw - Benz, Sebastian (GMS Medizin – Bibliothek – Information)
The Landesinitiative openaccess.nrw is a project of the Digitale Hochschule NRW (DH.NRW), which is a cooperative association of 42 universities in North Rhine-Westphalia, consisting of universities, universities of applied sciences, art and music colleges as well as private and church-run universities. It is funded by the NRW Ministry of Culture and Science. In a preliminary project, which included interviews with the university libraries and an online needs assessment, a large number of requirements for the state initiative were evaluated and the main project, which was launched in 2022, was aligned with the requirementrogram areas.